Availability and Utilization of E-Learning Technologies for Teaching Business Subjects in Secondary Schools in Anambra State, Nigeria - Gloria, Umelue, Ogochukwu (International Journal on Integrated Education, 2024)
The need to instill and engender efficiency and effectiveness in the implementation of curriculum for Business subjects calls for the utilization of e-learning technologies in instructional delivery. This study aimed to determine the extent of availability and utilization of e-Learning technologies for teaching of business subjects in the senior secondary schools in Anambra State. It specifically examined the extent of availability of e-Learning technologies; and assessed the extent utilization of various e-Learning technologies (hardware, software, and internet) by teachers of business subjects in the senior secondary schools in Anambra State. Four research question posed in line with the specific objectives guided the study; and has four corresponding hypotheses for mean differences. The study adopted a descriptive survey design to study a population of the 1260 out of which 164 samples were taken from the business subject teachers in Anambra State. The instrument for data collection is the Extent of E-learning Technologies Availability and Utilization Questionnaire (ETAUQ) structured in a Likert type format. The instrument was validated and have reliability of 0.9266 established using Cronbach Alpha. Data was analyzed using mean and standard deviation for the research questions and t-test for the hypotheses. The results showed that e-learning technologies availability at the secondary schools in Anambra State are considered to be at a moderate extent; e-learning hardware and software technologies were utilised at moderate extent; while the internet technologies was considered to be utilised at a low extent for teaching business subjects in the secondary schools in Anambra State. The hypotheses testing revealed that location (rural or urban) and gender (male and female) has no significant difference in the mean ratings of business subjects teachers on the extent of availability of e-Learning technologies for utilization; and the extent of utilization of e-Learning hardware technologies. However, teaching experience (above 10 years’ experience and below 10 years’ experience) in secondary schools in Anambra State differ significantly in their mean ratings on the extent of utilization of e-Learning software technologies in teaching. More is, business teachers with high qualification makes more effective utilization of the internet technologies than the low qualified business subject teachers in Anambra State. Among the recommendations were that curriculum planners should develop the curriculum that should include the use of e-learning technologies by secondary school teachers; and that secondary school administrators should sponsor the re-training of business subject teachers on the utilization of e-learning technologies in education so as to enhance their teaching skills.